Conducting publishable research under conditions of severely limited resources. Issue 1 (1st January 2020) - Bredan, Amin
ABSTRACT: Doing research when resources are severely limited will always be challenging. But by sharing resources, collaborating internationally as well as locally, developing sustainable research lines and optimizing study concept and design, researchers can significantly increase their research output and enhance its quality.